2002
DOI: 10.2136/sssaj2002.0254
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Controls on Soil and Whole-ecosystem Respiration from a Tallgrass Prairie

Abstract: ABSTRACTpiration and heterotrophic microbial respiration. Net ecosystem exchange of CO 2 as an integration of photoEnvironmental controls on C cycling in terrestrial ecosystems are synthesis, plant dark respiration, and soil respiration in difficult to define, because (i) C fluxes from plant vs. microbial activity are difficult to separate, and (ii) controlling variables are often intergrasslands can be obtained with various micrometeorocorrelated. We investigated temporal and spatial determinants of soil logi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
13
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 0 publications
5
13
0
Order By: Relevance
“…In general, an increase in soil temperature positively aff ected soil surface CO 2 effl ux when soil moisture was greater than 20%, but the opposite was true when soil moisture was <20%. Similar results were presented by Franzluebbers et al (2002). Additionally, across the entire growing season, certain plant species had lower soil surface CO 2 effl ux compared to other plant species (Table 4).…”
Section: Soil Surface Carbon Dioxide Effl Uxsupporting
confidence: 80%
“…In general, an increase in soil temperature positively aff ected soil surface CO 2 effl ux when soil moisture was greater than 20%, but the opposite was true when soil moisture was <20%. Similar results were presented by Franzluebbers et al (2002). Additionally, across the entire growing season, certain plant species had lower soil surface CO 2 effl ux compared to other plant species (Table 4).…”
Section: Soil Surface Carbon Dioxide Effl Uxsupporting
confidence: 80%
“…Carbon dioxide fl uxes were positively correlated with soil and air temperature and negatively correlated with soil moisture content, indicating an increase in CO 2 emissions with an increase in temperature and a decrease in soil moisture (Table 3). Similarly, an increase in CO 2 fl ux with an increase in soil temperature was also observed in agricultural (Mosier et al, 2006), tall grass prairie (Franzluebbers et al, 2002), and forest soils (Bowden et al, 1998). However, Shinjo et al (2006) observed CO 2 emissions related with soil temperature, but not with soil moisture content.…”
Section: Factors Aff Ecting Carbon Dioxide Methane and Nitrous Oxidmentioning
confidence: 73%
“…This is especially true for systems dominated by wet-dry cycles where a substantial contribution of soil micro-organisms to the CO 2 efflux is expected (Austin et al, 2004;Huxman et al, 2004a). However, some fraction of efflux should be related to the respiratory activity of plants and correlated with deeper, rooting zone soil moisture and transpiration (Franzluebbers et al, 2002;Chimner and Welker, 2005), and another fraction could be related to the release of CO 2 from the precipitation of carbonates in the soil profile during drying cycles (Emmerich, 2003).…”
Section: Introductionmentioning
confidence: 99%